Sound and space in La hora de los hornos/The Hour of the Furnaces. Issue 1 (1st March 2014) - Epplin, Craig
This article offers a detailed reading of the connections between sound and space in the 1968 film La hora de los hornos/The Hour of the Furnaces. Extant explorations of sound in this film tend to highlight the strategies of juxtaposition and commentary on the image track. Building on this scholarship, I propose that three uses of sound in particular – the narrative voice-over, dissonance with the image, and semi-diegetic music – correspond to the spatial imperatives of the film: its desire to forge alliances among disparate groups scattered throughout national and international space. This strategy is coherent with the express desire for the filmic experience to become a militant act, an intervention in the class war of 1960s Argentina. I conclude by positing that sonic elements together present an alternative to the vision-centric bias of critiques of late capitalism's dawn, something The Hour of the Furnaces shares with other representative films of same period in Latin America. Finally, I suggest that the analysis of sound in this film they highlights the sensorially embedded character of all filmic experience.